Aplicación web que permite la búsqueda centralizada y actualizada de los colegios a nivel Bogotá, Busco colegio (2021)
This document details the project "I am looking for a College" for the Specialization In Software Engineering from the Antonio Nariño University whose objective is develop a centralized and detailed school search engine for schools at the level Bogotá, where you seek to find the ideal school for the student supported by a search engine guided.